Metaphoric Reference: An Eye Movement Analysis of Spanish–English and English–Spanish Bilingual Readers - Heredia, Roberto R.; Cieślicka, Anna B. (Frontiers in Psychology, 2016)
This study examines the processing of metaphoric reference by bilingual speakers. English dominant, Spanish dominant, and balanced bilinguals read passages in English biasing either a figurative (e.g., describing a weak and soft fighter that always lost and everyone hated) or a literal (e.g., describing a donut and bakery shop that made delicious pastries) meaning of a critical metaphoric referential description (e.g., “creampuff”). We recorded the eye movements (first fixation, gaze duration, go-past duration, and total reading time) for the critical region, which was a metaphoric referential description in each passage. The results revealed that literal vs. figurative meaning activation was modulated by language dominance, where Spanish dominant bilinguals were more likely to access the literal meaning, and English dominant and balanced bilinguals had access to both the literal and figurative meanings of the metaphoric referential description. Overall, there was a general tendency for the literal interpretation to be more active, as revealed by shorter reading times for the metaphoric reference used literally, in comparison to when it was used figuratively. Results are interpreted in terms of the Graded Salience Hypothesis (Giora, 2002, 2003) and the Literal Salience Model (Cieślicka, 2006, 2015).